Ultrasound-Assisted Focused Open Necrosectomy in the Treatment of Necrotizing Pancreatitis - Pupelis, Guntars; Fokin, Vladimir; Zeiza, Kaspars; Kazaka, Ita; Pereca, Jelizaveta; Skuja, Vita; Boka, Viesturs (JOP. Journal of the Pancreas, 2015)
Context The surgical treatment of necrotizing pancreatitis includes percutaneous drainage of acute necrotic collections and sequestrectomy in the late phase of the disease. Objective The aim of the study was to compare the conventional open necrosectomy (CON) approach with the alternative focused open necrosectomy (FON) approach in patients with infected necrosis and progression of sepsis. Methods Patients with acute necrotizing pancreatitis were included in the study prospectively from January 2004 to July 2014. All patients had been admitted with the first or a new episode of disease. Symptomatic large fluid collections were drained percutaneously. The step-up approach was used in patients with several distant localizations of infected necrosis. The methods were analysed by comparing the individual severity according to the ASA, APACHE II and SOFA scores, infection rate, postoperative complication rate and mortality. Results A total of 31 patients were included in the FON group and 39 in the CON group. The incidence of infection was similar in groups. More ASA III comorbid conditions, a higher APACHE II score, a more frequent need for renal replacement therapy was observed in the CON group. The postoperative complication rate was in the range of 32% to 44%; mortality reached 6.5% in the FON group and 12.8% in the CON group. Conclusions Comorbid conditions, organ failure, and infection are the main risk factors in patients with necrotizing pancreatitis. The step-up approach and perioperative ultrasonography navigation improves the clinical outcome and reduces the extent of invasive surgical intervention in patients unsuited to other minimally invasive procedures. Image: Drainage of infected acute necrotic collection.